The impact of angiogenesis inhibitors on survival of patients with small cell lung cancer. (21st August 2019) - Shi, Xiaoshun; Dong, Xiaoying; Young, Sylvia; Chen, Allen Menglin; Liu, Xiguang; Zheng, Zhouxia; Huang, Kailing; Lu, Di; Feng, Siyang; Morahan, Grant; Cai, Kaican
Abstract: Background: Small cell lung cancer (SCLC) is a highly invasive and lethal neuroendocrine tumor. Antiangiogenic drugs have been reported in the treatment of SCLC. We aimed to provide a comprehensive evaluation of the impact of angiogenic inhibitors on SCLC survival using network meta‐analysis. Methods: The impact of five angiogenesis inhibitors, that is, vandetanib (Van), bevacizumab (Bev), Rh‐endostatin (End), sunitinib (Sun), and thalidomide (Tha), on progression‐free survival (PFS) and overall survival (OS) was evaluated by conducting a network meta‐analysis. RNA sequencing data were downloaded from publicly available databases. Results: Nine phase II and III randomized controlled trials (RCTs), that involved 1599 participants, that investigated angiogenesis inhibitors in the treatment of SCLC were included in this meta‐analysis. Sun and Bev achieved better PFS than Tha (Bev VS. Tha, HR = 0.88, 95% CI: 0.79‐0.98, Sun VS. Tha, HR = 0.80, 95% CI: 0.65‐1.00). Moreover, Sun and Bev were superior to placebo in terms of PFS (Bev VS. Placebo, HR = 0.89, 95%CI: 0.81‐0.97, Sun VS. Placebo, HR = 0.81, 95% CI: 0.66‐1.00). Based on this study, we found no significant difference of OS of SCLC. The angiogenesis pathway and expression of target genes were globally deactivated in SCLC tissue. Conclusion: Results of this network meta‐analysis indicate that the PFS outcome of SCLC with Sun or Bev drugs is superior to that of Tha. The improved therapeutic impact of angiogenesis inhibitors on SCLC needs more evidence, such as long‐term observation in clinical trials, to be validated. Abstract : In this manuscript, we performed the up‐to‐date comprehensive network meta‐analysis as well as bioinformatic analysis for the angiogenesis inhibitors on the survival of patients with small cell lung cancer in terms of both PFS and PS. Moreover, we found that the overall expression level of angiogenesis inhibitor targets is low expressed in SCLC tissue compared with matched normal tissue which could be the reason for the unideal response.